PERAN STRATEGIS LEMBAGA PENDIDIKAN ISLAM DI ERA MODERN DENGAN MENJEMBATANI TRADISI INOVASI - Vanya, Aprella Alivia; Fauzi, Nadhifa Azqia; Nova, Wanda Putri; Amrillah, Rizki (Relinesia: Jurnal Kajian Agama dan Multikulturalisme Indonesia, 2024)
The role of Islamic educational institutions in the modern era is pivotal, acting as a bridge between tradition and innovation. Through a comprehensive literature review, this study sheds light on the strategic significance of these institutions in integrating technological advancements while preserving traditional Islamic teaching methodologies. Embracing e-learning platforms, digital applications, and social media, these institutions have facilitated remote learning, particularly during the COVID-19 pandemic. However, they also uphold traditional methods like halaqah and talaqqi, which foster deep and personal learning environments. Furthermore, the curriculum has evolved to incorporate modern sciences alongside religious studies, aiming to produce graduates equipped with both religious knowledge and relevant skills for the contemporary job market. Additionally, Islamic educational institutions address contemporary social issues such as radicalism and social injustice, fostering a holistic approach to education. The study emphasizes the importance of continuous professional development for educators, active community involvement, and dynamic curriculum evaluation to ensure relevance and effectiveness in preparing students for the challenges of the modern world.